2012
DOI: 10.1007/s10728-012-0221-4
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Moral Status of Blood Donation

Abstract: The World Health Organisation encourages that blood donation becomes voluntary and unremunerated, a system already operated in the UK. Drawing on public documents and videos, this paper argues that blood donation is regarded and presented as altruistic and supererogatory. In advertisements, donation is presented as something undertaken for the benefit of others, a matter attracting considerable gratitude from recipients and the collecting organisation. It is argued that regarding blood donation as an act of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 68 publications
0
12
0
3
Order By: Relevance
“…Research has shown that many individuals cooperate on the condition that there is evidence or a good expectation that the other person will also cooperate (Gintis, 2000; Fischbacher et al, 2001; Nielsen et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that many individuals cooperate on the condition that there is evidence or a good expectation that the other person will also cooperate (Gintis, 2000; Fischbacher et al, 2001; Nielsen et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…De fato, a análise realizada no presente trabalho identificou a gratidão como central às questões de doação. Isso se confirma em estudos recentes sobre as distintas nuanças da gratidão manifestadas por doadores e receptores na doação de órgãos (O'Brien, Donaghue, Walker, & Wood, 2014), embriões (Scully, Haimes, Mitzkat, Porz, & Rehmann-Sutter, 2012) ou sangue (Snelling, 2014).…”
Section: Discussionunclassified
“…It might include the fixed smile and palpably false wish that a customer 'have a nice day' (Wang, 2016) but also acts similar to that performed by Simone's replacement. Although, unlike a compassionate act, a kind act might not be driven by desire (Phillips & Taylor, 2009) or virtue there is 22 In a similar vein, it has been argued that blood donation, considered and presented as supererogatory, should rather be considered as obligatory (Snelling, 2014). 23 Use of the word (in) appropriate also shows this circularity.…”
Section: The Negation Of Kindnessmentioning
confidence: 99%